Analisis Hidrofobisitas dan Estimasi Kekuatan Dielektrik Isolator Keramik 150kV dengan Pelapisan RTV-SiR+SiO₂ untuk Peningkatan Keandalan Sistem Transmisi Listrik - Ferdy Rahmat Hidayat; Yusreni Warmi; Sitti Amalia; Arifita Yuana Dewi Rachman (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
The primary challenge along the Koto Panjang–Payakumbuh transmission line is the elevated levels of pollution and humidity, which accelerate insulator surface degradation and increase the likelihood of flashover. This study aims to analyze the hydrophobicity characteristics and estimate the dielectric strength of 150-kV ceramic insulators before and after coating them with a mixture of RTV (Room Temperature Vulcanizing) silicone rubber and SiO₂ nanoparticles. The research employed a quantitative experimental approach in accordance with IEC TS 62073-2016. Hydrophobicity was evaluated using the sessile drop method, while the coating was applied through a spray-coating technique using a formulation of RTV-683, silica, hardener, thinner, and xylene. The results indicate a significant improvement in surface hydrophobicity, demonstrated by an increase in contact angle from an average of 72° to 113° after coating. The coated insulators also exhibited a reduction in leakage current of up to 46% compared to uncoated conditions, alongside an increase in dielectric strength from 73.58 kV to 163.70 kV. Empirical correlations reveal a strong relationship between enhanced hydrophobicity and improved electrical performance. The novelty of this study lies in its integrated evaluation of hydrophobicity and dielectric strength on ceramic insulators operating in tropical environments using RTV–SiO₂ nano-coating, an area that has received limited attention in previous research